Pengaruh Frekuensi Aktivitas Bercerita terhadap Kemampuan Menyimak Anak Usia Dini di Kelompok Bermain Salsabila 5 Purworejo - Susi Hendarti (STAI Al Mujtama Pamekasan, 2026)
This study investigates the influence of storytelling activity frequency on the listening comprehension skills of early childhood learners (aged 2–4 years) at Kelompok Bermain Salsabila 5 Purworejo. Using a qualitative case study approach with triangulation of data collection techniques—including observation, interviews, and documentation—this research involved 25 participants. Findings reveal that children exposed to high-frequency storytelling activities (five or more sessions per week) demonstrated significantly richer vocabulary, sustained attention spans, and improved narrative comprehension compared to their peers in lower-frequency groups. Three dominant patterns emerged: (1) phonological awareness developed through repetitive story structures; (2) pragmatic understanding was enhanced through interactive question-and-answer storytelling sessions; and (3) emotional engagement positively correlated with listening retention. These results underscore the critical role of systematic, frequent storytelling in fostering language acquisition during the sensitive developmental window of ages 2–4. Pedagogical implications for early childhood educators and curriculum designers are discussed, with particular emphasis on integrating structured storytelling routines into daily learning programs.